THE RELEVANCE OF WORKPLACE LEARNING IN GUIDING STUDENT AND CURRICULUM DEVELOPMENT - Nduna, N. J. (South African Journal of Higher Education, 2016)
In an attempt to demonstrate the relevance of workplace learning (previously known as ‘cooperative education’) in guiding student and curriculum development, this article presents findings from a research project on the current practice of workplace learning, drawn from an analysis of evaluation reports in a university of technology. Areas of improvement associated with current planning, implementation and evaluation of workplace education are outlined and reflected as student and curriculum development issues. The article calls for an alignment of academic and workplace practices for the mutual benefit of students and workplaces, for the use of the principle that workplace learning should be appropriate for a qualification and for interaction between the university and the workplace. The article also reflects on institutional attempts to address the shortcomings of current practice in response to the Higher Education Qualifications Framework (HEQF). Suggestions for improving workplace learning are also outlined. The article encourages partnerships, collaborative curriculum development and evaluation research and calls for a national strategy for managing the quality of workplace education.